TA’RIF AND TANKIR IN QUR’ANIC DISCOURSE: A LINGUISTIC STUDY OF CONTEXTUAL MEANING FORMATION - Siti Aminah; Lia Mahardika Harahap; Erka Pulungan; Agustiar (Al Ibrah: Journal of Arabic Language Education, 2026)
This study aims to analyse the function of ta’rif  wa tankir in the discourse structure of the Qur’an and to explain its contribution to the formation of contextual meaning from a Qur’anic linguistic perspective. This study is motivated by the tendency of previous research to treat ta’rif wa tankirprimarily as a grammatical and rhetorical phenomenon, whilst its role in meaning construction at the discourse level has received relatively little attention. The research employs a descriptive qualitative approach using library research. The research data consists of Qur’anic verses containing the phenomena of ta’rif wa tankīr, as well as various relevant literature in the fields of Qur’anic linguistics, semantics, pragmatics, discourse analysis, exegesis, and rhetoric. The data were analysed through the stages of data reduction, thematic categorisation, semantic and pragmatic interpretation, and discourse analysis to identify the relationship between the forms of maʿrifah and nakirah and the formation of contextual meaning. The results of the study indicate that ta’rif wa tankir not only function as markers of definiteness and indefiniteness, but also play a role in reference management, the organisation of information structure, the formation of semantic focus, the development of themes, and the construction of cohesion and coherence in Qur’anic discourse. This study found that the meaning produced by the maʿrifah and nakirah forms is dynamic and determined by the interaction between grammatical, semantic, pragmatic, and discourse-contextual aspects. The novelty of this research lies in the effort to reposition ta’rif wa tankiras a multidimensional linguistic mechanism functioning in the construction of contextual meaning at the discourse level, rather than merely a phenomenon of nahwu and balaghah. This study contributes to enriching the development of contemporary Qur’anic linguistics through the integration of semantic, pragmatic, and discourse analysis perspectives, whilst offering a new conceptual framework for understanding the relationship between definiteness, indefiniteness, and meaning formation in the Qur’an.